Long-term update of the 24954 EORTC phase III trial on larynx preservation. (September 2016) - Henriques De Figueiredo, B.; Fortpied, C.; Menis, J.; Lefebvre, J.L.; Barzan, L.; de Raucourt, D.; Geoffrois, L.; Giurgea, L.; Hupperets, P.; Leemans, C.R.; Licitra, L.; Rolland, F.; et al.
Abstract: The long-term results of the EORTC 24954 trial comparing sequential versus alternating chemotherapy and radiotherapy (RT) for patients with locally advanced laryngeal and hypopharyngeal cancer are reported. From 1996 to 2004, 450 patients were randomly assigned (1–1) to a sequential arm (SA = induction cisplatin-5fluorouracil followed by a 70Gy-RT for the responders or a total laryngectomy and post-operative RT for the non-responders) and an alternating arm (AA = cisplatin-5fluorouracil alternated with three 2-week courses of 20 Gy-RT for a total dose of 60 Gy). Median follow-up was 10.2 years. Ten-year survival with functional larynx (primary end-point) and overall survival were similar in both arms (18.7% and 33.6% in SA versus 18.3% and 31.6% in AA). Late toxicity was also similar; however, a trend for higher larynx preservation and better laryngeal function was observed in AA. Highlights: Sequential and alternating chemotherapy (CT) and radiotherapy (RT) have similar efficacy. A trend for a higher rate of larynx preservation is observed with alternating CT and RT. A trend for a better laryngeal function is observed with alternating CT and RT.